Agranulocytosis leads to intestinal Echinococcus multilocularis oncosphere invasion and hepatic metacestode development in naturally resistant Wistar rats. Issue 1 (22nd January 2021) - Joekel, Deborah E.; Nur, Selim; Monné Rodriguez, Josep; Kronenberg, Philipp A.; Kipar, Anja; LeibundGut-Landmann, Salomé; Deplazes, Peter
Abstract: Susceptibility to Echinococcus multilocularis infection considerably varies among intermediate (mostly rodents) and dead-end host species (e.g. humans and pig), in particular regarding intestinal oncosphere invasion and subsequent hepatic metacestode development. Wistar rats are highly resistant to infection and subsequent diseases upon oral inoculation with E. multilocularis eggs, however, after immunosuppressive treatment with dexamethasone, rats become susceptible. To address the role of the cellular innate immunity, Wistar rats were individually or combined depleted of natural killer (NK) cells, macrophages (MΦ) and granulocytes (polymorphonuclear cells, PMN) prior to E. multilocularis egg inoculation. Although NK cell and MΦ depletion did not alter the resistance status of rats, the majority of PMN-depleted animals developed liver metacestodes within 10 weeks, indicating that PMN are key players in preventing oncosphere migration and/or development in Wistar rats. In vitro studies indicated that resistance is not caused by neutrophil reactive oxygen species or NETosis. Also, light microscopical examinations of the small intestine showed that oral inoculation of E. multilocularis eggs does not elicit a mucosal neutrophil response, suggesting that the interaction of oncospheres and neutrophils may occur after the former have entered the peripheral blood. We suggest to consider granulocytes as mediators of resistance in more resistant species, such as humans.